The Law Enforcement Towards Foreign Vessels Which Did Illegal, Unreported and Unregulated Fishing (IUU-Fishing) In Indonesia Fisheries Management Areas - Belardo Prasetya Mega Jaya; Muhamad Uut Lutfi (Jurnal Dinamika Hukum, 2020)
Indonesia gets loss on some fields like economy, ecology, and social because of so many IUU-Fishing practices in Indonesia Fisheries Management Areas (FMA). Law enforcement is needed in handling the problem. Therefore, the aims of the research are : (1) to analyze how the law enforcement of foreign vessels which did IUU-Fishing in Indonesia Fisheries Management Areas (FMA) is inappropriate with the international law and the national law; (2)  to explain how  the procedure of law enforcement. This research used normative legal research. The result shows that Indonesia will act decisively every foreign vessels which did IUU-Fishing in Indonesia Fisheries Management Areas. Indonesia has enforced the law by burning and/or sinking every foreign vessel which did IUU-Fishing in Indonesian waters. Whereas in Indonesian Exclusive Economic Zone (IEEZ) would be punished by administrative sanctions and should pay a reasonable bond afterward the vessel and its crew would be deported to their country.